Turnover of Phosphatidylglycerol in Escherichia coli - Ballesta, J. P. G. (1973)
In growing cultures of Escherichia coli, the nonacylated glycerol of phosphatidylglycerol (PG) is labeled more rapidly than is the acylated glycerol. This is, in part, due to a rapid exchange reaction of the nonacylated glycerol. Only some of the PG molecules undergo this reaction while others are stable. Using a mutant unable to make glycerophosphate, we have shown that the nonacylated glycerol of PG can exchange with non-phosphorylated glycerol.